A chiral-at-metal asymmetric catalyzed vinylogous Michael addition of ortho-methyl aromatic nitro compounds for isoxazole derivative synthesis. Issue 15 (27th June 2019) - Li, Shi-Wu; Du, Yu; Kang, Qiang
Abstract : A chiral-at-metal rhodium(iii ) complex catalyzed asymmetric vinylogous Michael addition of 5-methyl 4-nitroisoxazoles with α, β-unsaturated 2-acyl imidazoles has been developed, delivering the corresponding adducts with up to 96% yield and 97% ee. Abstract : ortho -Alkyl aromatic nitro compounds as vinylogous nucleophiles in catalytic asymmetric synthesis have rarely been reported. Herein an asymmetric vinylogous Michael addition of 5-methyl 4-nitroisoxazoles with α, β-unsaturated 2-acyl imidazoles catalyzed by a chiral-at-metal rhodium(iii ) complex has been developed. The corresponding adducts were obtained in good yields (80–96%) with excellent enantioselectivities (up to 97%). The reaction can be conducted on a gram scale with a low catalyst loading (0.25 mol%) without impacting its efficiency.